PERANCANGAN MEDIA PEMBELAJARAN BERBASIS WEB DENGAN METODE SCRATCH UNTUK MENINGKATKAN PEMAHAMAN TEKNOLOGI SISWA DI SMP ISLAM BAHRUL ULUM - Muhammad Rafliansyah; Bayu Ardy Saputra; Ubaidillah; Muhammad Fikri; Khoirul Insanul Hamdi; Muhammad Ihsanul Hadi; Ahmat Zakaria Maulana; Rangga Rasendriya; Muhammad Harsyah; Aldefan Julian Syahputra; Dahlan Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This community service activity aims to design and implement web-based learning media using the Scratch programming method to enhance technology comprehension among students at SMP Islam Bahrul Ulum. The phenomenon of digitalization in education demands an adaptive and engaging learning approach to foster 21st-century skills, particularly in computational thinking and basic programming logic. The method applied in this service includes needs analysis, media design, implementation, and evaluation through pre-test and post-test instruments. Web-based learning media was developed using the Scratch platform, which provides an intuitive visual programming environment suitable for junior high school students. The results demonstrate a significant improvement in students' technology comprehension, reflected by an average N-Gain score of 0.67 (moderate category), and a highly positive response from participants toward the learning activities. This activity proves that web-based learning media utilizing Scratch is effective in fostering students' interest and understanding of information and communication technology in a fun, interactive, and structured learning environment.